2019
DOI: 10.1371/journal.pone.0199854
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis and confirmation of the type IV pili-associated proteins PilY1, PilW and PilV in Acidithiobacillus thiooxidans

Abstract: Acidithiobacillus thiooxidans is an acidophilic chemolithoautotrophic bacterium widely used in the mining industry due to its metabolic sulfur-oxidizing capability. The biooxidation of sulfide minerals is enhanced through the attachment of At. thiooxidans cells to the mineral surface. The Type IV pili (TfP) of At. thiooxidans may play an important role in the bacteria attachment since TfP play a key adhesive role in the attachment and colonization of different surfaces. In this work, we report for the first ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…We found that 22 genes in ‘cellular community‐prokaryotes’ and all genes related to ‘cell motility’ were downregulated (Fig. 6(d); Supporting Information, Table S9), showing that the virulence of Xcc was suppressed by ZnO QDs 50–55 . In addition, seven of nine genes related to ‘energy metabolism’ were downregulated (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We found that 22 genes in ‘cellular community‐prokaryotes’ and all genes related to ‘cell motility’ were downregulated (Fig. 6(d); Supporting Information, Table S9), showing that the virulence of Xcc was suppressed by ZnO QDs 50–55 . In addition, seven of nine genes related to ‘energy metabolism’ were downregulated (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…6(d); Supporting Information, Table S9), showing that the virulence of Xcc was suppressed by ZnO QDs. [50][51][52][53][54][55] In addition, seven of nine genes related to 'energy metabolism' were downregulated (Fig. 6(d); Supporting Information, Table S10).…”
Section: Stress Response Analysis Of Xcc Through Degsmentioning
confidence: 99%
“…Although the amount of carbohydrates and lipids maintain biofilm stability, proteins play a fundamental role in the attachment ( Tu et al, 2013 ). During cell attachment, outer membrane proteins from EPS and adhesins (Pili-associated proteins) molecularly interact irreversibly with the functional groups of the mineral, keeping cells attached ( Li et al, 2010 ; Chandraprabha and Natarajan, 2013 ; Alfaro-Saldaña et al, 2019 ). When comparing the composition of the EPS in 0.15% galactose-induced treatments, it is observed that the proteins increased by 60% for the induction with 18 g ⋅ L –1 of iron compared to the induction with 9 g ⋅ L –1 ( Table 2 ), suggesting a positive effect on attachment with protein increase.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of pili have been described according to their mechanisms of assembly, pilin structure, and morphology [ 1 ]. The type IV pili (T4P) are the most common filaments or fimbriae [ 15 ] and have been grouped based on the aminoacidic homology of the pilins, which are relatively conserved in Gram-negative bacteria [ 16 , 17 ], including chemolithoautotrophic acidophiles such as Acidithiobacillus ferrooxidans and A. thiooxidans [ 11 , 18 - 20 ]. All T4P share domain structures and preserved sequences such as the conserved N-terminal motif in major and minor pilins, which is a type III signal peptide [ 1 , 6 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is interesting is that the PilV of Acidithiobacillus species has been little described and analyzed. PilV of A. thiooxidans shares up to 93% homology with PilV of A. ferrooxidans in its mature form [ 20 ]. Recently we found that PilV is in a cluster fimT-pilW-pilV-pilX-pilY1 similar to the minor-pilins cluster of P. aeruginosa [ 32 ].…”
Section: Introductionmentioning
confidence: 99%